First phase insulin response in children with islet autoantibodies : results from the Finnish Type 1 Diabetes Prediction and Prevention study - Koskinen, Maarit (fi=Turun yliopisto|en=University of Turku|, 2019)
Type 1 diabetes results from the deficiency of insulin secretion from the pancreatic beta cells. The preclinical period of type 1 diabetes is characterized by the appearance of islet autoantibodies in the peripheral blood and appearance of two or more autoantibodies is highly predictive of clinical type 1 diabetes. The aim of this thesis was to investigate beta cell function in children from the Finnish Type 1 Diabetes Prediction and Prevention (DIPP) study. The DIPP study screens newborns for class II HLA associated risk for type 1 diabetes and follows children regularly. One or more intravenous glucose tolerance tests (IVGTTs) were performed for children who had developed islet autoantibodies. In progressors a declined first phase insulin response (FPIR) to glucose was observed 4-6 years prior to diagnosis as compared to non-progressors. Furthermore, in the age dependent comparison children progressing to T1D had lower FPIR than non-progressors throughout the whole childhood and this difference increased over time. When the association between FPIR and class II HLA was studied, it was observed that the class II HLA association was secondary to the appearance of autoantibodies. Declining pattern of FPIR was associated with multiple autoantibodies irrespective of class II HLA risk. Genetic variants outside the class II HLA region were, however, associated with the longitudinal pattern of FPIR. This study showed that in children that progress to clinical T1D the beta cell secretory capacity is reduced years before the onset of the disease. KEYWORDS: type 1 diabetes, beta cell function, insulin, glucose

Ensivaiheen insuliinivaste autovasta-ainepositiivilla lapsilla. Tuloksia suomalaisesta tyypin 1 diabeteksen ennustamis- ja ehkäisy (DIPP) –tutkimuksesta Tyypin 1 diabetes johtuu haiman betasolujen insuliinin erityksen puutteesta. Prekliinisenä aikana ennen tyypin 1 diabetesta perifeeriseen verenkiertoon ilmaantuu autovasta-aineita haiman saarekesoluja vastaan. Tyypin 1 diabeteksen riski on selkeästi lisääntynyt, kun lapselle on ilmaantunut kaksi tai useampi erilaista autovasta-ainetta. Tämän väitöskirjan tarkoituksena oli tutkia betasolujen toimintaa suomalaisen DIPP-tutkimuksen lapsilla. Yksi tai useampi suonensisäinen sokerirasituskoe tehtiin lapsille, joille oli ilmaantunut autovasta-aineita. Ensimmäisessä työssä tutkittiin glukoosin aineenvaihduntaa terveillä ja tyypin 1 diabetekseen sairastuvilla lapsilla. Sairastuvilla ensivaiheen insuliinivaste oli laskenut jo 4-6 vuotta ennen diagnoosia. Lisäksi iän mukaisessa vertailussa sairastuvilla lapsilla ensivaiheen insuliinivaste pysyi matalana koko lapsuuden ja ero ryhmien välillä kasvoi iän myötä. Kun tutkittiin luokan II HLA alueen ja ensivaiheen insuliinivasteen välisiä yhteyksiä, havaittiin, että yhteys johtui autovasta-aineista. Ajan myötä heikkenevä insuliinivaste oli yhteydessä kahden tai useamman autovasta-aineen esiintymiseen riippumatta luokan II HLA genotyyppiin liittyvästä riskistä. Muiden luokan II HLA alueen ulkopuolisten geneettisten varianttien ja insuliinivasteen välillä löytyi kuitenkin yhteyksiä. Tämä tutkimus osoitti, että lapsilla, jotka sairastuvat tyypin 1 diabetekseen betasolujen kyky erittää insuliinia on vähentynyt jo vuosia ennen kliinistä diagnoosia.